2022
DOI: 10.7717/peerj.12892
|View full text |Cite
|
Sign up to set email alerts
|

Micropropagation of pokeweed (Phytolacca americana L.) and comparison of phenolic, flavonoid content, and antioxidant activity between pokeweed callus and other parts

Abstract: Background Pokeweed (Phytolacca americana L.) is regarded as an invasive plant in many parts of the world but possesses therapeutic characteristics used for antitumor and rheumatism treatment. This study investigated the effects of auxins and four explants on pokeweed callus induction. The effects of cytokinins and combinations between cytokinins and NAA on shoot and root induction were also studied. TPC, TFC and antioxidant activity of calli were screened and compared with other pokeweed plant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
0
1
0
Order By: Relevance
“…However, not all auxins have the ability to induce adventitious root development. Trunjaruen et al [ 34 ] compared the effects of IBA and 2,4-dichlorophenoxyacetic acid (2,4-D) on pokeweed micropropagation. Their results showed that pokeweed roots were not observed in 2,4-D treatments.…”
Section: Resultsmentioning
confidence: 99%
“…However, not all auxins have the ability to induce adventitious root development. Trunjaruen et al [ 34 ] compared the effects of IBA and 2,4-dichlorophenoxyacetic acid (2,4-D) on pokeweed micropropagation. Their results showed that pokeweed roots were not observed in 2,4-D treatments.…”
Section: Resultsmentioning
confidence: 99%
“…Further, similar to our findings, cytokinins have been reported to increase the shoot length and leaf number in Phytolacca dodecandra (Chishimba et al, 1999). Kinetin also improved the shooting and leaf numbers in Phytolacca americana (Trunjaruen et al, 2022). The efficacy of applying cytokinins (kinetin) and GA 3 in promoting sprouting responses, root and shoot development among rhizome explants has been reported in several plant species, such as Pongamia pinnata (Sugla et al, 2007); Jurinea dolomiaea (Banday et al, 2014); Talinum triangulare (Swarna and Ravindhran, 2013); Picrorhiza kurroa (Patial et al, 2012) and Euphorbia wallichi (Hassan et al, 2020).…”
Section: Discussionmentioning
confidence: 96%